Effect of local topographic heterogeneity on tree species assembly in an Acacia-dominated African savanna. (11th March 2019) - Mutuku, Paul Musili; Kenfack, David
Abstract: Stand structure and tree species diversity patterns were examined plot-wide and among four topographically defined habitats (plateau, cliff, low plain and depressions) in a 120-ha permanent plot in an Acacia -dominated savanna in Mpala Ranch, central Kenya. The four habitats were defined by clustering the 3000 quadrats of 20 × 20 m in the plot based on their altitude, slope and convexity. Structural and floristic differences among the four habitats were examined and species-habitat associations were tested for the 30 most abundant species using torus translation randomization tests. The plot included 113 337 trees in 62 species with diameter at knee height ≥ 2 cm (18.4 species ha −1 ), 41 genera and 23 families. Fabaceae with the genus Acacia were the dominant family, followed by Euphorbiaceae and Ebenaceae. Tree density and basal area were twice as high on low plain and depressions than on the plateau. Species richness was highest in the cliff and was seven times higher than in the adjacent plateau. Half of the species assessed showed significant positive associations with one habitat and 21 showed significant negative associations with at least one habitat. The variation in stand structure and tree species diversity within the Mpala plot shows that topography is among the important drivers of local species distribution and hence the maintenance of tree diversity in savannas.